PENGARUH PSYCHOLOGICAL CONTRACT, JOB SATISFACTION, DAN ORGANIZATIONAL COMMITMENT TERHADAP KINERJA KARYAWAN PADA PEGADAIAN REGION MAKASSAR - Rulyana Ramadhani (Prodi Manajemen, 2024)
This research aims to examine the influence of Psychological Contracts, Job Satisfaction, and Organizational Commitment on employee performance at Pegadaian Region Makassar. The research method used is a quantitative approach by collecting data from 78 respondents who are employees of Pegadaian Makassar Region, using a certain sampling technique. Data collection was carried out through distributing questionnaires that measured these variables using a Likert scale. Data analysis was carried out using multiple linear regression to see the simultaneous influence of independent variables on the dependent variable. The results of the analysis show that the Psychological Contract, Job Satisfaction and Organizational Commitment have a significant positive effect on employee performance. This research provides important insights for management in improving employee performance by paying attention to psychological aspects and commitment to the organization. The results of this research show that there is a positive and significant influence of the Psychological Contract, Job Satisfaction, and Organizational Commitment on employee performance at PT Pegadaian Region Makasar. These findings underscore the importance of management relationships and communication between management and employees in the organizational context. By strengthening a positive psychological contract, increasing job satisfaction, and maintaining commitment to the organization, PT Pegadaian can optimize employee productivity and work quality.